CSR and CSRR in Kazakhstan: state and prospects - Brauweiler, Christian; Yerimpasheva, Aida (Społeczna odpowiedzialność biznesu i raportowanie społecznej odpowiedzialności biznesu w Kazachstanie: stan i perspektywy, 2019)
The state, business community and citizens are social partners in ensuring a better quality of life. Corporate social responsibility (CSR) is a mechanism for the interaction of these partners. Non-financial reporting is essentially a communication channel about corporate social responsibility, demonstrating information about the company’s market value, its impact on society and the environment. The use of CSR tools increases the level of confidence in business and ensures the sustainable development of society as a whole. The implementation of CSR strategy leads to increasing a company’s business reputation, which has a significant impact and allows the company to strengthen a position in the market. In the framework of the conducted research, we used secondary and primary data collection methods, as well, qualitative and quantitative. Kazakhstani companies are increasingly aware of the need to introduce CSR policies in their work and actively involved in the CSR reporting process. The topic of CSR is gaining popularity in Kazakhstan. Representatives of business, state, public, and consumers are increasingly gathering to discuss social projects
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 105-122
Keywords: corporate social responsibility; CSR; business ethics; corporate citizenship; Global Reporting Initiative; GRI; occupational health and safety; OH&S; społeczna odpowiedzialność biznesu; etyka w działalności gospodarczej; obywatelskie zaangażowanie przedsiębiorstw; zrównoważony rozwój; globalna inicjatywa sprawozdawcza; bezpieczeństwo i higiena pracy